The knowledge and prevalence of induced abortion among female undergraduates at a tertiary institution in Port Harcourt, Southern Nigeria - Kasso, Terhemen; Obidinnu, Elizabeth N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abortion is a sensitive and contentious issue with religious, moral, cultural, and political dimensions. Induced abortion especially when unsafe can endanger a woman’s reproductive health and lead to serious life-threatening complications and even death. This study was aimed at determining the knowledge and prevalence of induced abortion amongst female undergraduates at a tertiary institution in Port Harcourt, Nigeria. Methods: This was a descriptive cross-sectional study carried out on 303 female undergraduate students at the University of Port Harcort in November 2019. Data was collected using structured self-administered questionnaires and the information obtained was analysed with Statistical Package for Social Sciences (SPSS) version 23.0. Results: Majority of the respondents (93.1%) had good knowledge of abortion and most of them (96.4%) knew abortion as termination of pregnancy while 84.8% knew it to be illegal. Also, 25.7% had previously been pregnant with 79.5% of such pregnancies ending in induced abortion. This study noted that the age, level of study, religion, residence and family status of the respondents significantly influenced the practice of induced abortion (p<0.05). Conclusions: There was good knowledge of abortion and the complications of unsafe abortion among the respondents; however, many of them who had previously been pregnant had unsafe abortions. More awareness creation on the dangers of unsafe abortion and use of contraceptives especially the barrier methods among young people will significantly reduce the menace of unsafe abortion with its attendant complications.